Fit to play: practical tips for faster recovery (part 3) - Petersen, C.; Nittinger, N. (Medicine and Science in Tennis, 2006)
Developing an effective post training and competition routine is very important as it helps players recover physically and psychologically. Recovery sessions must be incorporated into sports specific training programmes. This approach to recovery and regeneration enhances athletic development and contributes to optimal performance.